A Learning Method to Improve Freestyle Swimming Technique in Beginner Athletes (Ages 9-12) Using Modified PVC Pipes - Tb. Rwindra Putra Lesmana; Rizal Ahmad Fauzi; Aam Ali Rahman (Tadulako Journal Sport Sciences And Physical Education, 2026)
The effectiveness of freestyle swimming learning for beginner athletes aged 9–12 years is often hampered, especially in hand movements or strokes, body alignment, motor coordination, and breathing control. This study used a convergent parallel mixed-methods design to test the effectiveness of land training based on modified PVC pipes (paralon) in improving freestyle swimming techniques in beginner athletes. A total of 10 participants were divided into experimental and control groups. Qualitative data were collected through observation, interviews, and documentation analyzed using NVivo 12, while quantitative data were analyzed using independent samples t-test and Cohen's d effect size. The results of the qualitative analysis identified the main obstacles to learning including body position misalignment, poor hand-foot coordination, flutter kick errors, insufficient arm thrust, inappropriate breathing patterns, and low self-confidence. Quantitatively, the experimental group experienced a significant increase in freestyle swimming performance compared to the control group (t(8) = −4.824, p = 0.001), with a very large practical effect (Cohen's d = 3.051). This finding indicates that the intervention is not only statistically significant, but also has a strong practical impact. The results of the study concluded that land training using modified PVC pipe media is an affordable, easily accessible, and highly effective teaching method for improving body position, movement coordination, breathing technique, self-confidence, and overall freestyle swimming performance in novice athletes.